2005
DOI: 10.1074/jbc.m500310200
|View full text |Cite
|
Sign up to set email alerts
|

Novelty of the Pyruvate Metabolic Enzyme Dihydrolipoamide Dehydrogenasein Spermatozoa

Abstract: Spermatozoa are cells distinctly different from other somatic cells of the body, capacitation being one of the unique phenomena manifested by this gamete. We have shown earlier that dihydrolipoamide dehydrogenase, a post-pyruvate metabolic enzyme, undergoes capacitation-dependent tyrosine phosphorylation, and the functioning of the enzyme is required for hyperactivation (enhanced motility) and acrosome reaction of hamster spermatozoa (Mitra, K., and Shivaji, S. (2004) Biol. Reprod. 70, 887-899). In this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 80 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Collectively, these results coupled with our findings indicate that all of the components of the (normally mitochondrial) pyruvate dehydrogenase complex, E1 (E1α [71] and E1β [24]), E2 (DLAT (this study Fig. 5E-H)], and E3 [dihydrolipoamide dehydrogenase [74]) are present in the principal piece of mammalian sperm. These results suggest that PDC in rodent sperm functions in the principal piece and may be important for sperm motility.…”
Section: Discussionsupporting
confidence: 75%
“…Collectively, these results coupled with our findings indicate that all of the components of the (normally mitochondrial) pyruvate dehydrogenase complex, E1 (E1α [71] and E1β [24]), E2 (DLAT (this study Fig. 5E-H)], and E3 [dihydrolipoamide dehydrogenase [74]) are present in the principal piece of mammalian sperm. These results suggest that PDC in rodent sperm functions in the principal piece and may be important for sperm motility.…”
Section: Discussionsupporting
confidence: 75%
“…Published literature provides precedence for extra-mitochondrial localization of PDH (Chueh et al, 2011; Mitra et al, 2005; Sutendra et al, 2014). Similar to our results in the pre-implantation embryo, all three subunits of PDH can be detected during the S phase of the cell cycle in the nucleus of lung cancer cell lines (Sutendra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ADT4 (Kim et al 2007), VDAC2 (Hinsch et al 2004), GAPDHS (Westhoff & Kamp 1997), hexokinase HK1 (Mori et al 1998, Travis et al 1998, AKAP4 (Turner et al 2001), dihydrolipoamide dehydrogenase acetyl transferase (Mitra et al 2005), carnitine acetyl transferase (Jeulin & Lewin 1996), 3-oxoacid CoA transferase (Koga et al 2000), tektin 3 (TEKT3; Wolkowicz et al 2002) (Brooks 1978), VDAC3 (Hinsch et al 2004), prohibitin (Thompson et al 2003), SMCP (Herr et al 1999), GPX4 (Nagdas et al 2005), have been reported earlier and were found to be present in testis and epididymis/ ejaculated sperm. The proteins ADT4 (Kim et al 2007) and VDAC2 (Hinsch et al 2004) have not been reported on head domain earlier.…”
Section: Discussionmentioning
confidence: 99%